Fundamental Analysis of Islamic Investment - Rahmi, Aida; Ibs, Juni Khairani; Rahmat, Paisal; Pulungan, Ahyar Hamdi (Al-Amien Prenduan for Islamic Institute, 2025)
This study discusses fundamental analysis in Islamic investment. Fundamental analysis is the main approach used by investors to assess whether sharia-compliant stocks are viable in the capital market. In this study, a literature review approach is adopted, drawing from various scientific articles and research related to fundamental analysis in Islamic investment. The findings indicate that fundamental analysis involves evaluating macroeconomic conditions, industry developments, and company financial statements. This helps investors reduce risks and increase the likelihood of gaining long-term profits. The application of fundamental analysis also requires investors to ensure that the selected companies are free from elements of riba (usury), gharar (uncertainty), and maysir (gambling or speculation), thereby complying with sharia criteria. Therefore, fundamental analysis in Islamic investment is a crucial element in making responsible and sustainable investment decisions in accordance with sharia principles.